Apparition, Time, and the Movement of The Chimes - Malton, Sara (Margins/Marges/Margini, 2025)
This contribution is a reading of Dickens’s The Chimes as a story of deprivation and starvation – of the mind, spirit, and the body. Throughout his fiction Dickens frequently presents his reader with a version of the moment in which one his character witnesses his own death, like in A Christmas Carol, The Signalman, A Tale of Two Cities. However, in The Chimes this episode is peculiarly dramatized given the text’s focus on starvation, deprivation, and exile. In fact, the protagonist’s encounter with his own dead body renders emphatically the degree to which the physical and the psychological are intimately linked; the deprivation, the starvation that necessarily drives such individuals onward from place to place produces a kind of psychological exile. At the end, all the forms of movement here represented are a function of the industrial, utilitarian context that Dickens’s tale seeks to indict. They underscore the invisibility of the poor as well as their exclusion from the regular movements of time that determine cultural ritual and the patterns of daily living, exiled as they are into a world of chaos.